The invisible Fran - Benton, Jim. (New York : Simon & Schuster Books for Young Readers, 2004)
When Franny Stein, self-styled mad scientist, creates a robot to show her school friends the joys of science, she ends up learning something from them instead.
840
Accelerated Reader AR
Keywords: Science fiction; Robots -- Fiction; Individuality -- Fiction; Schools -- Fiction